Fabrication of organic nanocomposite of polyaniline for enhanced electrochemical performance. (October 2020) - Kumar, M. Sathish; Das, Puspendu; Yasoda, K. Yamini; Kothurkar, Nikhil K.; Malik, Sudip; Batabyal, Sudip K.
Highlights: A simple and facile technique at 210 °C to obtain nano-structured organic compounds, instead of making carbon dots at a relatively higher temperature. This unique organic nanostructure utilized to make a composite of polyaniline and subsequently utilized as an active electrode material for supercapacitor applications. This composite material shows a substantial improvement in specific capacitance (779 F/g) and also discloses desirable capacitance retention (86.3%) using a three-electrode system. This composite used in a two-electrode solid-state symmetric device exhibits a gravimetric capacitance of 130 F/g and an areal capacitance of 650 mF/cm 2 . The cyclic stability of the symmetric device shows an excellent retention of 96% of the specific capacitance over 5000 cycles. Abstract: Herein, we have developed a simple and facile technique at 210 °C to obtain nano-structured organic compounds, instead of making carbon dots at a relatively higher temperature. Taking the advantage of stable dispersion of organic nanostructures in an aqueous medium, composite of polyaniline has been developed and subsequently utilized as an active electrode material for supercapacitor application. This composite material confirms noteworthy enhancement in specific capacitance (779 F/g) and also divulges the attractive capacitance retention using three-electrode systems. The suitability of the materials for the solid-state device was tested with a prototype two-electrode device. The symmetric device exhibits 130 F/g gravimetric capacitance and 650 mF/cm 2 areal capacitance. The improved performance in the specific capacitance is observed due to the generation of more active charge storage sites in the interfacial interaction of organic nanostructures and polyaniline in the composite. The cyclic stability of the symmetric device reveals excellent retention of 96% in specific capacitance over 5000 cycles. Graphical abstract: Image, graphical abstract